2011
DOI: 10.1016/j.aller.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of high-dose sublingual immunotherapy in children allergic to house dust mites in real-life clinical practice

Abstract: This retrospective study indicates that high-dose SLIT in children with rhinitis caused by house dust mites is well-tolerated and could be an effective treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
2
20
0
1
Order By: Relevance
“…In our cohort, both children and adults were included, and 52.3% had coexistent asthma. This prevalence, although greater than that seen in randomized studies on AR, is comparable with that seen in other real-life observational studies 17,2123. Prior to treatment initiation, we found that majority of the patients suffered a wide range of symptoms during the previous olive pollen season, with most reporting sleep disturbance and headache, which negatively impacted their daily activities.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our cohort, both children and adults were included, and 52.3% had coexistent asthma. This prevalence, although greater than that seen in randomized studies on AR, is comparable with that seen in other real-life observational studies 17,2123. Prior to treatment initiation, we found that majority of the patients suffered a wide range of symptoms during the previous olive pollen season, with most reporting sleep disturbance and headache, which negatively impacted their daily activities.…”
Section: Discussionsupporting
confidence: 84%
“…This schedule has been used and reported in a number of observational studies of this agent for allergic disease caused by other allergens 17,2123. Treatment was well tolerated, and the high level of compliance across 2 years (98.8%) indicates that treatment was acceptable to both patients and (in the case of children) their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies in this pediatric population indicate that HDM-based SLIT significantly reduces the number of acute asthma attacks [169], the duration and dose of ICS [170], and symptomatic medication use [171]. In contrast, Ferrés et al [172] did not find any improvement in asthma severity. When SLIT efficacy and safety was compared in monosensitized and polysensitized children, the significant improvement in global clinical parameters was similar in both groups [173].…”
Section: Pediatric Populationsmentioning
confidence: 99%
“…It has been well established that SLIT requires a high allergen dose for its efficiency to facilitate a take-up of sufficient amounts of allergens by sentinel dendritic cells within the oral mucosa or due to a lack of adjuvants by sublingual administration [46]. Even though a high dose and long courses of medication are necessary, SLIT is a safe therapeutic option for children, as has been recently reported by Ferrés et al [47]; although, in this study, the mild and local adverse reaction rate was at 23%; however, none of the cases from the study group showed an anaphylactic reaction. Similarly, in the clinical study by Eifan et al [40] it was demonstrated that SLIT was associated with clinical improvement and proved to be a safe mode of immunotherapy.…”
Section: Mucosal Tolerance: An Implication For Sublingual Immunothmentioning
confidence: 99%